On the Possibility of Using Succinate in Hypoxia Developing in COVID-19 - Yu. P. Orlov; N. V. Govorova; O. V. Korpacheva; V. V. Afanasyev; I. A. Khilenko (Общая реаниматология, 2021)
Aim. To provide a rationale for the feasibility of using the succinate-containing drugs to treat hypoxia associated with COVID-19 based on the analysis of experimental and clinical studies.Materials and methods. 84 Russian and international literature sources concerning the pathogenesis of COVID-19 and the pathogenetic role of succinate in the management of COVID-19 associated hypoxia, oxidative stress and diaphragmatic dysfunction were analyzed. The literature search was performed using Pubmed and ELIBRARY.ru databases.Results. The literature analysis showed that tissue hypoxia, triggering the pathomorphological cascade of events and resulting in multiple organ failure is a central element of COVID-19 pathogenesis. Experimental and clinical studies show the positive impact of tissue hypoxia correction using succinate in both adult patients and children with various conditions associated with acute respiratory failure.Conclusion. The literature data provide a rationale for using succinate-containing drugs in the treatment of severe COVID-19.